Glandless cotton - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
The latest strains of glandless cotton, which produce as much fibre as the more conventional strains, are now being tested in the Cote d'lvoire in order to verify their agronomic and technological performance. Similar work is being done to test...